Correlations between aerobic exercise time during physiotherapy and characteristics of patients with subacute stroke: A pilot cross-sectional study. (1st February 2023) - Nozoe, Masafumi; Masuya, Rio; Yamamoto, Miho; Kubo, Hiroki; Kanai, Masashi; Shimada, Shinichi
ABSTRACT: Background: The amount of aerobic exercise time (AET) is an important factor for improving physical function in patients with stroke. However, there is a lack of evidence regarding the factors for AET during physiotherapy, particularly in stroke patients. Objective: To investigate the correlation between AET during physiotherapy and characteristics of patients with subacute stroke. Methods: In this cross-sectional study, 61 hospitalized subacute stroke patients (age = 72 (11) years, (median (interquartile range)) were enrolled and their exercise intensity was measured by wearable sensors (Mio Alpha 2) worn during physiotherapy sessions. All patients were divided into two groups, non-ambulatory group (functional ambulation classification (FAC); 0–2) and ambulatory group (FAC; 3–5). The correlations between AET and patient characteristics were assessed in each group. Results: There was no significant difference in AET between the ambulatory and non-ambulatory groups (9 (12) min vs 5 (10) min, p = .27, respectively). There was a significant correlation between AET and the functional independent measures (FIM) motor score in the ambulatory group (r = 0.52, p = .005), and between AET and the FIM cognitive score in the non-ambulatory group (r = 0.44, p = .008). Conclusion: Correlations between AET and patient characteristics were different according to ambulation capacity in patients with subacute stroke.